32ps timing jitter with a fully integrated front end circuit and single photon avalanche diodes - G. Acconcia; I. Rech; I. Labanca; M. Ghioni (Electronics Letters)
Excellent performance of custom technology SPAD detectors have been widely demonstrated in recent years. Low‐jitter timing measurements with these detectors require front end electronics able to sense the avalanche current at a very low level when the multiplication process is still confined in a very small area around the photon absorption point. Best in class results (35 ps full width at half maximum) have been obtained with discrete circuits not suitable to be used in densely integrated systems of SPAD arrays required by modern demanding applications. A new fully integrated front end able to read out the avalanche current with a timing jitter as low as 32 ps and suitable to be exploited with SPAD arrays is presented.